2019
DOI: 10.1002/mrm.28010
|View full text |Cite
|
Sign up to set email alerts
|

An orthogonal shim coil for 3T brain imaging

Abstract: We designed and implemented an orthogonal shim array consisting of shim coils with their planes perpendicular to the planes of neighboring RF coils. This shim coil improves the magnetic field homogeneity by minimizing the interference to RF coils. Methods: Using realistic off-resonance maps of the human brain, we first evaluated the performance of shim coils in different orientations. Based on simulations, we developed a 7-channel orthogonal shim array, whose coil plan was perpendicular to neighboring RF coils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…The five most inferior and posterior neck loops were not set up for shimming based on (i) the difficulty of running wires all the way through the coil to these loops, and (ii) preliminary B 0 shimming simulations suggesting that they provide only minor gains for B 0 ‐shim performance. To bring the number of shim channels up to 31, six multi‐turn shim‐only loops were added over the face area to target prefrontal cortex, an idea previously explored experimentally by Juchem et al 33 and Zhou et al, 34 as well as in simulations 1 . These 4‐ to 6‐cm dia.…”
Section: Methodsmentioning
confidence: 99%
“…The five most inferior and posterior neck loops were not set up for shimming based on (i) the difficulty of running wires all the way through the coil to these loops, and (ii) preliminary B 0 shimming simulations suggesting that they provide only minor gains for B 0 ‐shim performance. To bring the number of shim channels up to 31, six multi‐turn shim‐only loops were added over the face area to target prefrontal cortex, an idea previously explored experimentally by Juchem et al 33 and Zhou et al, 34 as well as in simulations 1 . These 4‐ to 6‐cm dia.…”
Section: Methodsmentioning
confidence: 99%
“…10 shows that strong inhomogeneity regions still remain even after global shimming at very high degree. And although inhomogeneity values at and geometry in some studies [11,29,44].…”
Section: Whole-brain B0 Homogeneity Limitsmentioning
confidence: 99%
“…To mitigate this issue, dynamic B 0 shimming with a custom-built 32-channel integrated ΔB 0 /Rx array (AC/DC coil) 54 was used to reduce the B 0 inhomogeneity and hence the level of distortion differences between the blip-up/down data. Our previous study 45 showed that use of the dynamic B 0 shimming method [55][56][57] with the AC/DC coil 54 could significantly mitigate the local field inhomogeneity by more than 50%, which when combined with advanced parallel imaging can enable dMRI acquisition with single-shot EPI at about 8× distortion mitigation compared with the nonaccelerated single-shot EPI with standard second-order shim. This includes a factor of approximately 2× distortion reduction from improved B 0 homogeneity achieved by the AC/DC coil compared with baseline global shimming with the scanner's built-in first/second-order spherical harmonic shims.…”
Section: Combining Gslider With Buda-epimentioning
confidence: 99%